Clinical efficacy of botulinum toxin type A in patients with traumatic brain injury, spinal cord injury, or multiple sclerosis: An observational longitudinal study - Baricich, Alessio; Battaglia, Marco; Cuneo, Daria; Cosenza, Lucia; Millevolte, Marzia; Cosma, Michela; Filippetti, Mirko; Dalise, Stefania; Azzollini, Valentina; Chisari, Carmelo; Spina, Stefania; Cinone, Nicoletta; et al. (Frontiers in Neurology, 2023)
Botulinum toxin type A (BoNT-A) is the treatment of choice for focal spasticity, with a concomitant effect on pain reduction and improvement of quality of life (QoL). Current evidence of its efficacy is based mainly on post stroke spasticity. This study aims to clarify the role of BoNT-A in the context of non-stroke spasticity (NSS). We enrolled 86 patients affected by multiple sclerosis, spinal cord injury, and traumatic brain injury with clinical indication to perform BoNT-A treatment. Subjects were evaluated before injection and after 1, 3, and 6 months. At every visit, spasticity severity using the modified Ashworth scale, pain using the numeric rating scale, QoL using the Euro Qol Group EQ-5D-5L, and the perceived treatment effect using the Global Assessment of Efficacy scale were recorded. In our population BoNT-A demonstrated to have a significant effect in improving all the outcome variables, with different effect persistence over time in relation to the diagnosis and the number of treated sites. Our results support BoNT-A as a modifier of the disability condition and suggest its implementation in the treatment of NSS, delivering a possible starting point to generate diagnosis-specific follow-up programs. Clinical trial identifier NCT04673240.